Pengetahuan Masyarakat Tentang Daun Sirsak Untuk Hipertensi - Susilo Yulianto (Jurnal Kebidanan dan Kesehatan Tradisional, 2019)
Public Knowledge About Soursop Leaves For Hypertension. Hypertension is a condition in which blood pressure is higher than 140/90 millimeters of mercury (mmHG). The 140 mmHG number refers to systolic reading, when the heart pumps blood throughout the body. Meanwhile, the 90 mmHG number refers to diastolic reading, when the heart is relaxed while refilling its chambers with blood. Based on a preliminary study conducted by the researchers, the data about people's knowledge about soursop leaves for hypertension was very diverse. The purpose of this study was to find out public knowledge about soursop leaves for hypertension. This research is a quantitative descriptive study with a cross sectional approach. The sampling technique uses quota sampling with 30 respondents. Data analysis was carried out by descriptive analysis. The results of data analysis showed that respondents who had good knowledge were 27 respondents (90%), while respondents who had sufficient knowledge were 3 respondents (10%). The conclusion of this study is that public knowledge about soursop leaves for hypertension, is in the good category (90%), and knowledge with sufficient category (10%).